Semiotics of Transformation: A Saussurean and Peircean Analysis of Kafka’s The Metamorphosis - Muhammad Aria Ekaputra (Morphosis: Journal of Literature, 2025)
This research presents a comprehensive semiotic analysis of Franz Kafka's The Metamorphosis, drawing on both Saussurean and Peircean semiotics. By applying various semiotic theories, the study explores the complementary dimensions of meaning within the text, focusing on the multi-layered sign systems present in physical transformation, the disruption of language, social hierarchies, and familial dynamics. This examination demonstrates that Kafka’s work incorporates both arbitrary and intentionally constructed sign systems, creating a complex network of meaning that reflects broader themes of alienation, identity, and societal structures. Ultimately, this paper argues that the intersection of Saussurean and Peircean perspectives offers new insights into the mechanisms through which literature generates and communicates meaning through diverse, interrelated systems of signs.